2018
DOI: 10.3390/ma11071201
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Apatite Containing Statin Enhances Bone Formation in Healing Incisal Extraction Sockets in Rats

Abstract: The purpose of this study was to evaluate the feasibility of using apatite blocks fabricated by a dissolution–precipitation reaction of preset gypsum, with or without statin, to enhance bone formation during socket healing after tooth extraction. Preset gypsum blocks were immersed in a Na3PO4 aqueous solution to make hydroxyapatite (HA) low crystalline and HA containing statin (HAFS), or in a mixed solution of Na2HPO4 and NaHCO3 to make carbonate apatite (CO) and CO containing statin (COFS). The right mandibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Hydroxyapatite (Ca10(PO4)6(OH)2) can remineralize lost or damaged bone tissue without causing a rejection reaction by the body. Bioactive properties of hydroxyapatite can help bind them to bone tissue and provide specific biological responses that can stimulate osteoblast cells to produce new bone tissue so that it can help the process of bone regeneration [8,31]. Analysis with SAA showed a hydroxyapatite surface area of 0.50 m 2 /g, a pore size of 123.20 nm, and a pore volume of 31.02 mm 3 /g.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite (Ca10(PO4)6(OH)2) can remineralize lost or damaged bone tissue without causing a rejection reaction by the body. Bioactive properties of hydroxyapatite can help bind them to bone tissue and provide specific biological responses that can stimulate osteoblast cells to produce new bone tissue so that it can help the process of bone regeneration [8,31]. Analysis with SAA showed a hydroxyapatite surface area of 0.50 m 2 /g, a pore size of 123.20 nm, and a pore volume of 31.02 mm 3 /g.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis research conducted by Bassir et al (2018) concluded that the preservation of alveolar bone using bone graft material effectively minimizes the reduction in the vertical and horizontal dimensions of post-extraction alveolar bone [4]. Alveolar bone preservation using bioactive ingredients is also expected to accelerate the time required for post-extraction bone healing for prosthodontic purposes [27].…”
Section: Alveolar Bone Preservationmentioning
confidence: 99%
“…In the paper by Rakhmatia et al [12], an investigation into how statins can enhance bone formation was carried out. This was executed by evaluating how readily apatite blocks made via a dissolution-reprecipitation reaction, involving preset gypsum in the presence and absence of statins, could increase bone formation in a socket healing scenario after tooth extraction.…”
Section: Synopsis Of Papers Contributed To the Special Issuementioning
confidence: 99%